Heterogeneity of cancer‐associated fibroblasts: Opportunities for precision medicine - Kanzaki, Ryu; Pietras, Kristian (Cancer science, 2020)
Despite marked development in cancer therapies during recent decades, the prognosis for advanced cancer remains poor. The conventional tumor–cell‐centric view of cancer can only explain part of cancer progression, and thus a thorough understanding of the tumor microenvironment (TME) is crucial. Among cells within the TME, cancer‐associated fibroblasts (CAFs) are attracting attention as a target for cancer therapy. However, CAFs present a heterogeneous population of cells and more detailed classification of CAFs and investigation of functions of each subset is needed to develop novel CAF‐targeted therapies. In this context, application of newly developed approaches to single‐cell analysis has already made an impact on our understanding of the heterogeneity of CAFs. Here, we review the recent literature on CAF heterogeneity and function, and discuss the possibility of novel therapies targeting CAF subsets. The conventional tumor–cell‐centric view of cancer can only explain a part of cancer progression, thus understanding of the tumor microenvironment (TME) is crucial. Among cells within the TME, cancer‐associated fibroblasts (CAFs) are attracting attention as a target for cancer therapy. Here, we review the recent literature that has improved our understanding of heterogeneity in CAFs and function of each subset, and discuss the possibility of novel therapies targeting CAF subsets.